Lindgren, Raymond (audio interview #1 of 1) - Lindgren, Raymond (2/10/1913 - 4/13/1995); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This single interview with Raymond Lindgren was conducted in the CSULB Oral History Resource Center. The audio quality is good. 3/23/1981